Comprehensive Assessment of the Possibility of Using Waste Water for Irrigation Purposes - Umbetova, Sh.M.; Utegulov, N.I.; Olzhabaeva, A.O.; Zarbaliev, M.C.; Otarbayev, B.S.; Nakipova, Zh.K. (Herald of Azerbaijan Engineering Academy, 2024)
Currently, there is a shortage of water resources in 6 out of 8 water management basins of the Republic of Kazakhstan, and the expected trends in the growth of water consumption, both in Kazakhstan and in neighboring countries, will lead to an even greater increase in water consumption deficit. This will be due to both a decrease in available water resources and an increase in their consumption. Therefore, the main efforts should be directed to: efficient use of water resources in reclamation systems with the use of modern water-saving irrigation and reclamation technologies; stimulating water conservation in all sectors of the economy.